1980
DOI: 10.1136/hrt.43.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Five-year survival of 728 patients after myocardial infarction. A community study.

Abstract: The mortality also was higher for recurrent acute myocardial infarctions than for first attacks. The fiveyear mortality for women was less (20.5%, age-adjusted) than for men (31-6%). This is mainly because of the higher incidence of nontransmural infarcts in women. Acute ischaemic heart disease is more common, more often fatal, and has a poorer long-term prognosis in men than in women in Helsinki. The acute mortality from acute ischaemic heart disease is high in Helsinki when compared with other WHO registers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(33 citation statements)
references
References 26 publications
1
31
1
Order By: Relevance
“…9,26 However, several studies 9,15,16,[18][19][20][21]25 of predictors for case fatality and survival rates in MI were hospital based. Some studies included only subjects who initially survived a heart attack, 11,14,19,21 measured risk factors after the first event, 9,11,19 or included first and recurrent attacks, 3,18,20 although a study among survivors may not reveal the most important causes of a fatal outcome in MI. Community-based studies of risk factors for case fatality and survival rates after heart attacks are few.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,26 However, several studies 9,15,16,[18][19][20][21]25 of predictors for case fatality and survival rates in MI were hospital based. Some studies included only subjects who initially survived a heart attack, 11,14,19,21 measured risk factors after the first event, 9,11,19 or included first and recurrent attacks, 3,18,20 although a study among survivors may not reveal the most important causes of a fatal outcome in MI. Community-based studies of risk factors for case fatality and survival rates after heart attacks are few.…”
Section: Discussionmentioning
confidence: 99%
“…1,[8][9][10][11][12] Factors that are known to influence the case fatality rate are an advanced age, 1,3,[12][13][14][15] a previous infarct, 1,10,12,14 and diabetes mellitus. 10,[16][17][18] Some studies claim that women fare better 11,14,17,18 or worse 19,20 than men after a major heart attack, while others [21][22][23][24][25] found no independent effect of sex. The size and location of an infarct are important immediate predictors for subsequent death.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of the myocar dium to compensate for the infarcted muscle mass may contribute to haemodynamic im balance in AMI patients [17], Obstructive coronary artery disease seems to be more severe in patients who have an old myocar dial infarct lesion than in those who have none [25]. The prognostic significance of re current infarctions has, in fact, been shown in follow-up studies of AMI patients [15,20,21]. The progress of coronary care is thus controversial since improvement in the sur vival of an acute attack increases the pool of patients most susceptible to death in associa tion with the next attack.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates were reported to be 12% in the 1st year, 33% in the 5th year and 48% in the 9th year [11], 11% in the 1st year, 30.1% in the 5th year [12], 9% in the 1st year, 14% in the 3rd year [3], The lst-year mortality in our population was similar to that of Davis et al [3], but was relatively lower than those of most of the other studies [5,11,12], Cumula tive mortality rates within 3, 5 and 10 years were also found to be lower than previously reported rates [11,12], Differences in the studied populations might influence direct comparison of mortali ty rates. There were age restrictions in most of the reported studies [3,[11][12][13][14], It is known that advanced age is associated with higher mortality. Although patients older than 70 years were not excluded from this study, mor tality rates were found to be lower than in some of the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%